The role of pancreatic enucleation in the minimally invasive era - Yiannakopoulou, Eugenia (Laparoscopic Surgery, 2018)
We appreciate the invitation to comment on the article “Minimally invasive versus open pancreatic enucleation. Systematic and meta-analysis of surgical outcomes” published in the Journal of Surgical Oncology (1). In this systematic review, the authors aimed to compare the surgical outcomes of minimally invasive pancreatic enucleation versus open pancreatic enucleation., with the primary outcome being the comparative rate of postoperative pancreatic fistula (POPF) between the two approaches. The authors concluded that minimally invasive surgery is not at higher risk of POPF.